2021
DOI: 10.3390/ph15010029
|View full text |Cite
|
Sign up to set email alerts
|

Nano Differential Scanning Fluorimetry-Based Thermal Stability Screening and Optimal Buffer Selection for Immunoglobulin G

Abstract: Nano differential scanning fluorimetry (nanoDSF) is a high-throughput protein stability screening technique that simultaneously monitors protein unfolding and aggregation properties. The thermal stability of immunoglobulin G (IgG) was investigated in three different buffers (sodium acetate, sodium citrate, and sodium phosphate) ranging from pH 4 to 8. In all three buffers, the midpoint temperature of thermal unfolding (Tm) showed a tendency to increase as the pH increased, but the aggregation propensity was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Analysis of the protein domain organization of OvoA Th2 suggests that similar to that of OvoA Eta , OvoA Th2 has both sulfoxide synthase and methyltransferase domains (Figure S1). Due to thermostability concerns in OvoA crystallization, after overexpression and purification of OvoA Th2 (Figure S2) using a protocol similar to those employed for OvoA Eta and OvoA Mtht characterization, , we assessed the thermostability of OvoA Th2 using a nanoDSF assay (Figure B). , The thermal unfolding curves of the peptide of OvoA Mtht are included for comparison purposes. Our analysis demonstrated that the T M of OvoA Th2 is approximately 21 °C higher than that of OvoA Mtht (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the protein domain organization of OvoA Th2 suggests that similar to that of OvoA Eta , OvoA Th2 has both sulfoxide synthase and methyltransferase domains (Figure S1). Due to thermostability concerns in OvoA crystallization, after overexpression and purification of OvoA Th2 (Figure S2) using a protocol similar to those employed for OvoA Eta and OvoA Mtht characterization, , we assessed the thermostability of OvoA Th2 using a nanoDSF assay (Figure B). , The thermal unfolding curves of the peptide of OvoA Mtht are included for comparison purposes. Our analysis demonstrated that the T M of OvoA Th2 is approximately 21 °C higher than that of OvoA Mtht (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Thermal differential scanning fluorimetry (DSF) measurements were performed using a Prometheus NT.48 (NanoTemper Technologies, Germany) equipped with back-reflection technology for high-throughput analysis of unfolding temperature (T m ), calculated from the intrinsic fluorescence intensity ratio of tyrosine and tryptophan (350/330 nm). 40 Prior to each experiment, the excitation power was set to achieve ≥5,000 counts in the discovery scan. Corresponding profiles were analysed in Prometheus NT.48 and the first derivative calculated.…”
Section: Methodsmentioning
confidence: 99%
“…The intrinsic fluorescence from unfolding events exposing tyrosine and tryptophan residues were monitored via the 350/330 nm intensity ratio. 12 A temperature ramp of 2°C/minute from 20-95 °C was performed. Both samples were assessed at concentrations ~150 mg/mL and unfolding temperatures of antibody domains (T m1 , T m2 and T m3 ) detected from first-derivative peaks of the 350/330 nm fluorescence intensity ratio.…”
Section: (3)mentioning
confidence: 99%